Impact of ion temperature anisotropy on 2D edge-plasma transport. (March 2021) - Zhao, M.; Jaervinen, A.E.; Joseph, I.; Rognlien, T.D.
Abstract: A model of ion temperature anisotropy for 2D plasma transport in the scrape-off layer (SOL) of tokamaks is described and implemented in the UEDGE fluid transport code. Two ion energy equations are used to describe the evolution of the separate parallel and perpendicular ion temperatures. The temperature anisotropy generates viscous forces in both parallel and perpendicular directions that modify the parallel force balance equation and add an additional cross-magnetic-field drift velocity. Using the full set of UEDGE plasma and neutral equations (particle continuity, momentum, and energy), simulations are performed for both a 1D poloidal case and a 2D (radial and poloidal) single-null tokamak geometry case to highlight the 2D effects. The results show that ion parallel flows near the magnetic X-point in a comparatively low collisionality regime can be overestimated by the standard isotropic Braginskii model. The 2D ion temperature anisotropy varies substantially near the X-point and also near the divertor target plates, due to ionization sources. Moving radially outwards at the outer midplane, the anisotropy decreases between the core boundary and the magnetic separatrix and then it increases while moving across the SOL to the chamber wall. Highlights: The ion temperature anisotropy model is implemented in UEDGE and is adapted to UEDGE physics model with currents, drifts and neutral recycling. The model is used to study a real tokamak geometry. General structures of the ion temperature anisotropy and its effects on plasma profiles are identified in a tokamak geometry.